Disruption of Nuclear Factor-Interleukin-6, a Transcription Factor, Results in Severe Mycobacterial Infection - Sugawara, Isamu (American Society for Investigative Pathology, 2001)
Nuclear factor-interleukin-6 (NF-IL-6) is one of several nuclear transcription factors (NF-IL-6, NF-κB, PU.1, interferon-regulatory factor 1, Egr-1, and Stat-1). NF-IL-6 and NF-κB are expressed in macrophages and is induced by bacterial lipopolysaccharides. To evaluate whether NF-IL-6 is required for the inflammatory immune response to mycobacterial infection, in which epithelioid macrophages comprise the leading cell population, we generated NF-IL-6 knockout (KO) mutant mice. Airborne infection of these mice with Mycobacterium tuberculosis strains induced disseminated tuberculosis lacking granuloma formation, although interferon-γ, tumor necrosis factor-α, and interleukin-12 mRNA expression levels were within the normal range compared with those of wild-type mice. Generation of O(2)(−) and mycobacterial killing by neutrophils from these mice were impaired severely compared with wild-type mice. We conclude that NF-IL-6 is a critical transcription factor in mycobacterial control as well as in granulocyte-colony stimulating factor induction resulting in neutrophil activation.